An approach to feature moving of hexahedral mesh. (February 2019) - Shen, Chun; Wang, Rui; Gao, Shuming; Maehama, Hiroki
Abstract: In the product design process, the finite element mesh regeneration is an inevitable step, but it is time consuming. The mesh editing is a kind of effective mesh regeneration technique. In this paper, a method for large scale feature movement of hexahedral mesh is proposed to satisfy application requirement. After the feature moving operation is applied to CAD model, the mesh deformation based on the mean value coordinates is carried out in the corresponding deformed region of the hex mesh to decrease the possible inverted elements caused by a large scale deformation. Then, the parameters of generating the density field are extracted from the initial hexahedral mesh, and used to calculate the local target density field by considering the geometric and topological information on the deformed region. Finally, based on difference between current density field and target density field of deformed region, the local refining and coarsening operations are devised and conducted to make the deformed region compatible with the target density field. Experimental results for the mechanical parts verify the effectiveness of proposed method. Highlights: A method to deal with a large scale feature movement of hex mesh. Reduction of inverted elements using mesh deformation based on MVC. Calculation of target density field by analyzing the sizing properties of the original mesh. Mesh density adjustment by well devised local refining and coarsening operations.